Spectrum of hospitalized NeuroCOVID diagnoses from a tertiary care neurology centre in Eastern India. (November 2021) - Bhansali, Sakhi; Bagrodia, Vaishali; Choudhury, Supriyo; Rahman, Simin; Golder, Mohua; Tiwari, Mona; Kumar, Hrishikesh
Highlights: Stroke and encephalopathy are common NeuroCOVID emergencies in India. NeuroCOVID can manifest without pre-existing systemic and neurological comorbidities. NeuroCOVID can occur concurrently or prior to classical features of COVID-19. Abstract: Purpose: To describe the spectrum of hospitalized NeuroCOVID on admission in a tertiary neurology centre in Kolkata, the largest and most populated metropolitan city in Eastern India. Method: We retrospectively studied confirmed COVID-19 patients admitted with a neurological condition from 1st May 2020 to 30th January 2021. Neurological diagnoses and their temporal relationship to respiratory features along with clinicodemographic profile for such patients was ascertained. Result: 228 patients were diagnosed with NeuroCOVID at our centre. Of the 162 included population (median age was 59 (50–70) and 62.3% (1 0 1) were male) and 73.5% were diagnosed with NeuroCovid before any respiratory or febrile features. 46 patients (28.8%) had a pre/co-existing neurological illness, and 103 (63.6%) had systemic comorbidities. No significant difference was observed when comparing demographics and comorbidities of NeuroCOVID patients presenting with and without fever and respiratory features. Moreover, no individual NeuroCOVID diagnosis was more prone to present with respiratory or febrile features. Diabetes mellitus was the only comorbidity which was significantly higher in the ischemic stroke group, all other comorbidities and characteristics were evenly distributed between stroke and non-stroke NeuroCOVID patients and encephalopathy non encephalopathy NeuroCOVID patients. Conclusion: Stroke and encephalopathy are the most prevalent parainfectious neurological conditions occurring with COVID-19 in the Indian population. This study demonstrates seemingly low-risk individuals (i.e. people without pre-existing systemic and neurological comorbidities) may develop neurological conditions. Moreover, NeuroCOVID may manifest independent of respiratory features and fever.